Effectiveness of different types of toothbrushes on periodontal health in orthodontic patients with gingivitis: A randomized controlled study - Gokce Aykol-Sahin; Busranur Ay-Kocabas; Banu Mert; Hande Usta (BMC, 2024)
Abstract Background The aim of the study is to evaluate the effectiveness of different toothbrushes in reducing gingival inflammation and dental biofilm removal in gingivitis patients with fixed orthodontic appliances. Methods Following baseline clinical assessments, including the Turesky modification of the Quigley-Hein plaque index (TQHI), gingival index (GI), bleeding on probing (BOP), and probing pocket depth (PPD), all patients received nonsurgical periodontal therapy. Patients were then randomly assigned to one of three groups: conventional toothbrush (C-TB), orthodontic toothbrush (O-TB), or single-tufted toothbrush (ST-TB). Each group received tailored oral hygiene instructions based on their assigned toothbrush type. Clinical assessments were repeated and recorded in the first week, sixth week, and third month. Results Thirty-six patients with a mean age of 23.14 ± 3.86 (18-32 years) participated in the study. All groups with twelve patients each demonstrated significant improvements in clinical parameters compared to baseline. In the sixth week, the O-TB and ST-TB groups showed significantly greater improvements in TQHI and BOP scores compared to the C-TB group (p < 0.05). By the third month, the ST-TB group maintained significantly lower TQHI and BOP scores, while the O-TB group's scores became similar to those of the C-TB group. ST-TB and C-TB groups had significantly lower GI scores than the O-TB group in all time points. Although the effectiveness of ST-TB was significantly higher than that of other toothbrushes, all toothbrushes demonstrated lower efficacy in the posterior region. Conclusions The ST-TB was shown to be more effective in reducing gingival inflammation over three months, while it demonstrated similar efficacy to the O-TB in dental biofilm removal. Further research is necessary to substantiate these findings and to demonstrate the efficacy of this approach in promoting periodontal tissue health in patients with fixed orthodontic appliances. Trial registration This study was registered with the National Library of Medicine Clinical Trials Registry Platform on 19/07/2024 as NCT06510179.